The Predictive Value of Integrated Pulmonary Index after Off-Pump Coronary Artery Bypass Grafting: A Prospective Observational Study - Fot, Evgenia V.; Izotova, Natalia N.; Yudina, Anjelika S.; Smetkin, Aleksei A.; Kuzkov, Vsevolod V.; Kirov, Mikhail Y. (Frontiers in Medicine, 2017)
Background: The early warning scores may increase the safety of perioperative period. The objective of this study was to assess the diagnostic and predictive role of Integrated Pulmonary Index (IPI) after off-pump coronary artery bypass grafting (OPCAB). Materials and methods: Forty adult patients undergoing elective OPCAB were enrolled into a single-center prospective observational study. We assessed respiratory function using IPI that includes oxygen saturation, end-tidal CO2, respiratory rate and pulse rate. In addition, we evaluated blood gases and hemodynamics, including ECG, invasive arterial pressure and cardiac index. The measurements were performed after transfer to the ICU, after spontaneous breathing trial (SBT) and at 2, 6, 12, and 18 hrs after extubation. Results and Discussion: The value of IPI registered during respiratory support correlated with cardiac index (rho = 0.4; p = 0.04) and ScvO2 (rho = 0.4, p = 0.02). After extubation, IPI values decreased significantly, achieving a minimum by 18 hrs. The IPI value ≤ 9 at 6 hrs after extubation was a predictor of complicated early postoperative period (AUC = 0.71; p = 0.04). Conclusions: The Integrated Pulmonary Index is associated with changes in cardiac output and may predict the postoperative complications after OPCAB